Improved Adipocyte Viability in Autologous Fat Grafting With Ascorbic Acid–Supplemented Tumescent Solution. Issue 4 (October 2019) - Lunger, Alexander; Ismail, Tarek; Todorov, Atanas; Buergin, Joel; Lunger, Fabian; Oberhauser, Ida; Haug, Martin; Kalbermatten, Daniel Felix; Largo, Rene Denis; Martin, Ivan; Scherberich, Arnaud; Schaefer, Dirk Johannes
Abstract : Introduction: In reconstructive surgery, fat volume augmentation is often necessary for esthetic or functional reasons. As an alternative to synthetic and xenogeneic materials, autologous fat grafting (AFG) based on liposuction is gaining popularity, yet successful transplantation and long-term volume maintenance are difficult. Standard tumescent solution formulations neglect adipocyte and stromal vascular fraction (SVF) cell survival during extraction, as well as SVF differentiation into adipocytes thereafter, all of which are crucial for the success of AFG. Here we hypothesized that addition of ascorbic acid (AA) to the tumescent solution could prevent liposuction-induced cell damage. Materials and Methods: The effect of 0.1 mmol/L AA in tumescent solution was investigated in a previously described ex vivo model of AFG. Briefly, excision fat was infiltrated with tumescent solution, with or without AA, and incubated for 20 minutes at 37°C. Hand-assisted liposuction was then performed with a blunt cannula. Total cell viability, clonogenicity, and differentiation capacity of the SVF cells were assessed. Results: With AA, 10.3% more cells and in particular 14.9% more adipocytes survived liposuction. Clonogenicity, adipocyte and osteoblast differentiation by SVF cells remained unchanged. Conclusions: Addition of AA successfully improved survival of adipocytes during liposuction without affecting SVF growth and differentiation. This study therefore identified a useful supplement to the tumescent solution which may lead to improving AFG success.